The Effect of the Quality of Services on the Visitors’ Satisfaction and Desire to Pay a Revisit to the Bali Pulina Agrotourism - Purnami, Ni Nyoman Alit; Oka Suryawardani, I Gusti Ayu (E-Journal of Tourism, 2018)
The perception of the visitors of the quality of the services provided at the Bali Pulina Agrotourism contributed to their satisfaction, which would then make them desirous of paying a revisit to it. The research was conducted at the Bali Pulina Agrotourism. This study was intended to analyze the effect of the quality of services (physical evidence, reliability, responsiveness, assurance, and empathy) on the visitors? satisfaction with the Bali Pulina Agrotourism, and analyze the effect of the visitors? satisfaction on their desire to pay a revisit to it. The respondents in this study were the tourists who had visited the Bali Pulina agrotourism, totaling 80 and obtained using the accidental sampling method. The model was designed based on the Smart PLS version 3.0-based Structural Equation Modelling (SEM) using a computer program. The results of the study showed that physical evidence significantly contributed to the visitors? satisfaction (p = 0.002); reliability significantly contributed to the visitors? satisfaction (p = 0.005); responsiveness significantly contributed to the visitors? satisfaction (p = 0.040); assurance significantly affected the visitors? satisfaction (p = 0.001); empathy significantly affected the visitors? satisfaction (p = 0.014); the visitors? satisfaction significantly contributed to their desire to pay a revisit to the Bali Pulina Agrotourism (p = 0,000). Based on the results of the study, the Bali Pulina Agrotourism was expected to be able to maintain and improve the quality of services to make the visitors feel satisfied and desirous of paying a revisit. Keywords: agrotourism, service quality, satisfaction, revisit, PLS